Comparison of Corticosteroids Versus Platelet-Rich Plasma for the Treatment of Plantar Fasciitis: A longitudinal Study - Lachman Das Maheshwari, Muhammad Younis, Muhammad Shuaib Chandio, Sajjad Hussain Bhatti, Syed Muhammad Khalid Karim, Hussain Bux Palh, Niaz Hussain Keerio, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare the effectiveness of corticosteroids therapy and platelet-rich plasma (PRP) therapy for the treatment of plantar fasciitis. Study design: A longitudinal study Place and Duration: This study was conducted at Liaquat University of Medical and Health Sciences Jamshoro Pakistan from June 2020 to June 2021 Methodology: A total of 120 participants were considered in the study. Participants were divided into two groups. Both groups consisted of 60 patients each. One group was treated with corticosteroids injection (n=60) and the other was treated with PRP (n=60). All the participants were assessed clinically at the time of induction of treatment, after six weeks of the treatment, and after six months of the treatment. The clinical assessment included the visual analog pain scale (VAS), Roles and Maudsley scoring, and the American Foot & Ankle Society (FAS). Results: A significant improvement in plantar fascia thickness, VAS, and AFAS was observed after the injection was given to the participants of both groups. The mean AFAS of the PRP group at 6th week was 84.6±4.8 and in the sixth month, it was 90.4±2.9. The value of AFAS of the corticosteroid group at 6th week was 75.3±4.7 and it was 80.1±4.2 in the sixth month. The mean value of VAS in the PRP group at the 6th week was 2.5±1 and at the 6th month was 1±0.7. Likewise, the value of VAS in the corticosteroid group at 6th week was 4±1.2 and at 6th week was 2.7±0.8. There were no complications in both groups. Conclusion: The corticosteroids injection and PRP injection have the same effectivity for the treatment of plantar fasciitis.